Construction and Building Materials - Somarathna, H.M.C.C.; Raman, S.N.; Mohotti, D.; Mutalib, A.A.; Badri, K.H. (University of Jaffna, 2021)
Experimental investigation was conducted using concrete specimens to assess the effectiveness of bio based polyurethane (PU) coating synthesized from palm kernel oil in enhancing the dynamic mechanical response of concrete specimens under quasi-static and dynamic loads. The dynamic loading condition was simulated by conducting three-point bending tests at a strain rate of 0.067 s 1 , and simultaneously, under quasi-static loading (strain rate of 0.00033 s 1 ) conditions. The application of PU layer(s) (either on the impact face, rear face, or on both faces of the concrete specimens) increases the dynamic resistance of the concrete element, which can be enhanced by increasing coating thickness on either face of the con crete element. Under dynamic conditions, with 10% of total coating thickness compared to the beam depth, strain during ultimate failure, and strain energy density were enhanced significantly with mar ginal enhancement in the ultimate flexural strength. PU coating does not debond during ultimate failure of the test specimens which implies good adhesion characteristics, and even with minimum coating thickness (2.5%), drastic fragmentation effects can be reduced. Bio-based PU is a green material and appli cation of PU coating provides a viable and sustainable technique for protecting concrete structures against dynamic loads
Keywords: bio-based Polyurethane elastomer; coating thickness: Concrete; dynamic loading; retrofitting